Carboxymethyl cellulose-grafted mesoporous silica hybrid nanogels for enhanced cellular uptake and release of curcumin - Tiwari, Neha; Nawale, Laxman U.; Sarkar, Dhiman; Badiger, Manohar V. (Gels, 2017)
Mesoporous silica nanoparticles (MSNs) with ordered pore structure have beensynthesized and used as carriers for the anticancer drug curcumin. MSNs were functionalizedwith amine groups and further attached with carboxymethyl cellulose (CMC) using 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) coupling chemistry, which increased the hydrophilicityand biocompatibility of MSNs. The functionalized MSNs (MSN-NH2and MSN-CMC) werecharacterized using Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM),Dynamic Light Scattering (DLS), N2adsorption, X-Ray Diffraction (XRD), Thermo GravimetricAnalysis (TGA) and Fourier Transform Infrared Spectroscopy (FT-IR). Thein vitrorelease of curcuminfrom the –NH2and CMC functionalized MSNs (MSN-cur-NH2and MSN-cur-CMC) was performedin 0.5% aqueous solution of sodium lauryl sulphate (SLS). The effect of CMC functionalization ofMSNs towards cellular uptake was studied in the human breast cancer cell line MDA-MB-231 andwas compared with that of MSN-NH2and free curcumin (cur). Both MSN-NH2and MSN-CMCshowed good biocompatibility with the breast cancer cell line. The MTT assay study revealedthat curcumin-loaded MSN-cur-CMC showed better uptake as compared to curcumin-loadedMSN-cur-NH2. Free curcumin was used as a control and was shown to have much less internalizationas compared to the curcumin-loaded functionalized MSNs due to poor bioavailability. Fluorescencemicroscopy was used to localize the ﬂuorescent drug curcumin inside the cells. The workdemonstrates that CMC-functionalized MSNs can be used as potential carriers for loading and releaseof hydrophobic drugs that otherwise cannot be used effectively in their free form for cancer therapy.